2012
DOI: 10.17925/ohr.2012.08.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia in Cancer Patients

Abstract: Anemia is defined by the World Health Organization as a hemoglobin (Hb) level <13 g/dl for men and <12 g/dl for women, 1 and can be further subcategorized into mild (>10 g/dl), moderate (8-10 g/dl), severe (6.5-8 g/dl), and life-threatening (<6.5 g/dl) ranges. Anemia is a common comorbidity in cancer patients. In the previously mentioned ECAS study, cancer-related anemia was most frequently reported in patients with gynecological cancer (81.4 %), lung cancer (77 %), and lymphoma/myeloma (72.9 %). 2 In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…11 In addition, anaemia is a recognized complication of myelosuppressive chemotherapy, and it has been estimated that around 1.3 million cancer patients who are not anemic at the time of diagnosis may acquire anaemia during the course of their disease in the United States. 12 Most studies have found that pretreatment anaemia is an important predictor of prognosis, survival, and disease free period. 13 Grigieneet al and Zhang et al, in their study found that the hemoglobin (Hb) level before treatment had a significant influence on overall survival, disease-free survival and local relapse-free survival in uterine cervical carcinoma treated with irradiation 14 and Breast Cancer 13 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, anaemia is a recognized complication of myelosuppressive chemotherapy, and it has been estimated that around 1.3 million cancer patients who are not anemic at the time of diagnosis may acquire anaemia during the course of their disease in the United States. 12 Most studies have found that pretreatment anaemia is an important predictor of prognosis, survival, and disease free period. 13 Grigieneet al and Zhang et al, in their study found that the hemoglobin (Hb) level before treatment had a significant influence on overall survival, disease-free survival and local relapse-free survival in uterine cervical carcinoma treated with irradiation 14 and Breast Cancer 13 , respectively.…”
Section: Introductionmentioning
confidence: 99%